Psychological Distress Amongst Medical Laboratory Professionals Involved in COVID-19-Related Duties: A Nationally Stratified Cross-Sectional Survey, Ghana - Swithin M. Swaray; John Tetteh; George Ekem-Ferguson; Ignatius A. N. Awinibuno; Dennis Adu-Gyasi; Franklyn Acheampong; Alfred Edwin Yawson (SAGE Publishing, 2021)
To assess the prevalence and factors associated with psychological distress (PD) and Medical Laboratory Professionals (MLPs) involvement in COVID-19-related duties. This study adopted an online cross-sectional, nationally stratified survey among 473 MLPs using Google Form with a designated link; Depression, anxiety, and stress scale-21 (DASS-21) was used to measure depression, anxiety, and stress (secondary outcome). We employed generalized Negative Binomial (NBR) and Poisson regression analytical approach to our study outcomes. All analyses were performed using Stata 16, and P -value≤.05 deemed significant. The overall DASS-21 score ranged from asymptomatic psychological distress to severe symptomatic PD. The prevalence of depression, anxiety, and stress were 9.1 [95%CI=6.8-12.0], 17.8 [95%CI=14.6-21.5], and 7.5 [95%CI=5.4-10.1], respectively. The result evinced a high and significant association; the univariate NBR predicted a significant increase of PD score by 12% and 18% among participants who were involved in one and two or more COVID-19-related duties, respectively, (β[95%CI] = .12 [.05-.18] and .18 [.10-.26], respectively). A binary outcome predicted approximately 2-folds of overall psychological distress among participants involved in two or more COVID-19-related duties compared with non-involvement (adjusted Prevalence Ratio [95%CI]= 2.34 [1.12-4.85]). For depression, anxiety, and stress symptoms, both univariate and multivariate data analyses evinced a higher disadvantage among MLP involved in COVID-19-related duties. We observed a high tendency of experiencing significant psychological distress amongst MLP involved in COVID-19-related duties. Experience of psychological distress increased with deeper involvement in COVID-19-related activities. Psychological support should be extended to MLPs to limit the effect of these negative emotions on their cognitive and social behavior as well as job performance.